Design and Development of a Novel Universal Gripper Having Rigid Mechanics With Self-Adaptable Fingers for Industrial Applications - Muhammad Usman Khalid; Michal Jilich; Mattia Frascio; Benoit Levesque; Alessandro Zanella; Matteo Zoppi (IEEE Access, 2025)
In industrial assembly, intralogistics, and powertrain automation, it is essential to implement robust, safe, and efficient object-grasping solutions that are applicable to various scenarios. From this perspective, the design, kinematic analysis, and experimental evaluation of a novel three-finger universal gripper are presented in this paper. The aim of this research is to develop and validate a versatile grasping solution that combines the precision of rigid mechanics with the adaptability of soft robotics for handling diverse industrial components ranging from delicate items to complex automotive parts. The rigid mechanical structure of each finger integrates a Chebyshev-parallelogram linkage mechanism with thermoplastic polyurethane (TPU) finger for object interface. The gripper design addresses the challenge of handling diverse components through three key innovations integrated into a cohesive system: 1) a compound linkage mechanism that transforms the linear input at the Chebyshev linkage into angular motion driving the parallelogram linkage interfaced with the self-adaptable finger, maintaining near-perfect linear motion (±0.033 mm deviation) with a 6.06:1 mechanical advantage; 2) a modular design enabling rapid reconfiguration between parallel, equiangular, and envelope grasping configurations; and 3) independent actuation of each finger for asymmetric object handling. Moreover, the Fin Ray–inspired fingertip enables an overall lightweight gripper design with firm grasping capability, self-adaptivity, and finer object manipulation. Three soft finger designs were characterized through compression testing at multiple positions, revealing significant performance differences, with one finger demonstrating superior overall performance and selected for gripper integration. Tensile pull-out tests using the equiangular configuration demonstrated retention capabilities with peak forces of 45-77 N and sustained forces of 15-25 N, translating to practical load capacities of 1.5-2.5 kg. Furthermore, the gripper’s performance was validated through integration with a six degrees of freedom (6DOF) industrial robot, grasping objects ranging from delicate items like an orange to automotive components like a clutch plate. Objects weighing up to approximately 2.5 kg were grasped reliably, whereas objects exceeding 3 kg showed minor occasional slippage. The universal gripper weighs less than 3 kg and features integrated stepper motors with Modbus RTU control, thus offering a practical solution for industrial environments requiring versatile and adaptive handling.